Penguatan Nilai Kearifan Lokal â€œPoda Na Limaâ€ Dalam Pembentukan Karakter Generasi-Z Desa Lintongnihuta Kecamatan Ronggurnihuta Kabupaten Samosir - Naibaho, Zanrison; Marlina, Murni Eva; Pasaribu, Payerli; Malau, Waston (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Lintongnihuta Village, Ronggurnihuta District, Samosir Regency is a partner village that is the target audience for the Community Partnership Program with the activity of Implementing Local Wisdom Values "Poda Na Lima" in forming the character of the z generation. Generation-Z of the people of Lintongnihuta Village cannot be separated from very advanced technological developments, this has a negative impact on the character of the younger generation if it is not balanced with strengthening local wisdom values that have been passed down from their ancestors. The community partnership program activity of implementing the local wisdom values "Poda Na Lima" in forming Generation-Z's character offers several alternative solutions, including: providing outreach about the urgency of Generation-Z's character amidst the development of information technology. Providing assistance to Generation-Z, through seminars, discussions and mutual cooperation in cleaning the surrounding environment.